Hercules - Dubowski, Cathy East (New York : Disney Enterprises, 1997)
Young Hercules knew he didn't fit in with the other kids his age, who called him Jerk-ules. But he had no idea he was born, Pain and Panic, Hades' not-so-bright helpers, tranformed Hercules into a mortal instead of actually killing him.
Based on the Walt Disney Pictures movie, the heroic and humorous novel contains eight pages of full-color stills from the animated film.
Keywords: Hero -- Fiction; Humorous -- Novel